2021
DOI: 10.1111/joor.13237
|View full text |Cite
|
Sign up to set email alerts
|

Survey of oral hypofunction in older outpatients at a dental hospital

Abstract: Background Oral hypofunction is defined as the reversible stage preceding oral dysfunction. However, its assessment and management need further examination and consideration. Objective The present study aimed to examine the current state of oral hypofunction among outpatients at the university hospital. Methods New outpatients underwent medical interviews and detailed assessment of oral hypofunction at their initial visit to our dental department. Oral hypofunction was diagnosed if the results of three of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…Additionally, the incidence of oral hypofunction among older adults living in other regions has been reported to be 35.9%–63.0%. 11 , 13 , 38 , 39 , 40 The prevalence of oral hypofunction was within the range reported previously, as were the prevalence of sarcopenia and oral hypofunction. Those results were obtained by integrating data from rural (39.2%) and urban (60.8%) areas to reduce regional bias.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, the incidence of oral hypofunction among older adults living in other regions has been reported to be 35.9%–63.0%. 11 , 13 , 38 , 39 , 40 The prevalence of oral hypofunction was within the range reported previously, as were the prevalence of sarcopenia and oral hypofunction. Those results were obtained by integrating data from rural (39.2%) and urban (60.8%) areas to reduce regional bias.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the prevalence of oral hypofunction was 38.4%. Additionally, the incidence of oral hypofunction among older adults living in other regions has been reported to be 35.9%–63.0% 11,13,38–40 . The prevalence of oral hypofunction was within the range reported previously, as were the prevalence of sarcopenia and oral hypofunction.…”
Section: Discussionsupporting
confidence: 73%
“…This was thought to be due to the fact that the participants in our study were all outpatients visiting a dental hospital. However, the rate was only 36% in a previous study that included dental hospital outpatients [19]. This could be attributed to the older participants in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…Although they were relatively old, they had few diseases, other than hypertension, that could affect their oral function and were considered robust older adults. It has been reported that the oral hypofunction test results could be easily influenced by dental complaints [19]. However, dental complaints vary greatly among patients and are difficult to analyze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation